Thermomechanical analysis of porous solid oxide fuel cell by using peridynamics - Hanlin Wang; Erkan Oterkus; Selahattin Celik; Serkan Toros (AIMS Energy, 2017)
Solid oxide fuel cell (SOFC) is widely used in hybrid marine propulsion systems due to its high power output, excellent emission control and wide fuel suitability. However, the operating temperature in SOFC will rise up to 800–1000 ℃ due to redox reaction among hydrogen and oxygen ions. This provides a suitable environment for ions transporting through ceramic materials. Under such operation temperatures, degradation may occur in the electrodes and electrolyte. As a result, unstable voltage, low capacity and cell failure may eventually occur. This study presents thermomechanical analysis of a porous SOFC cell plate which contains electrodes, electrolytes and pores. A microscale specimen in the shape of a plate is considered in order to maintain uniform temperature loading and increase the accuracy of estimation. A new computational technique, peridynamics, is utilized to calculate the deformations and stresses of the cell plate. Moreover, the crack formation and propagation are also obtained by using peridynamics. According to the numerical results, damage evolution depends on the electrolyte/electrode interface strength during the charging process. For weak interface strength case, damage emerges at the electrode/electrolyte interface. On the other hand, for stronger interface cases, damage emerges on pore boundaries especially with sharp corner.